INHIBITORY EFFECT OF RED PIPER BETEL LEAF ETHANOL EXTRACT (PIPER CROCATUM RUIZ AND PAV.) AGAINST TRICHOMONAS VAGINALIS TROPHOZOITES IN VITRO - Kusuma, Sri Agung Fitri; Manan, Widyastuti S; Budiman, Fajar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this study is to determine the minimum inhibitory concentration (MIC) of red betel leaf ethanol extract against Trichomonas vaginalis trophozoites. Materials and Methods: The samples of red piper betel leaf were extracted with 70% ethanol using a maceration method. The phytochemical screening of ethanol extract was performed using the standard procedures. Isolation of T. vaginalis trophozoites from vaginal secretions was conducted using swab method, then suspending it into a saline solution sterile and followed by observing trophozoites motility using a microscope. While the anti-leucorrhea activity test and determination of MIC extract was done using macrodillution method. The inhibitory effect of each extract concentration to trichomonas trophozoites' morphology was observed under a microscope using staining techniques by adding Giemsa dyes. Results: The extract of red piper betel leaves contains several secondary metabolites such as alkaloids, flavonoids, polyphenols, quinones, and saponins. Of the six vaginal secretions, four positive trichomoniasis secretions were obtained. The results of anti-leucorrhea activity of red piper betel ethanol extract showed that the number of inactive trophozoites was proportional to the increasing of extract concentration. The inactive trophozoites were characterized by the absence of its motility under microscope observation. The MIC value of red piper betel extract of T. vaginalis trophozoites was 5% w/v. Conclusion: It can be concluded that the ethanol extract of red piper betel leaves could be contribute as a natural and safe anti-leucorrhea candidate for in vivo study on trichomoniasis in the future.